2004
DOI: 10.1186/1471-2091-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of exposed hydrophobic amino acids to arginine to increase protein stability

Abstract: BackgroundOne strategy to increase the stability of proteins is to reduce the area of water-accessible hydrophobic surface.ResultsIn order to test it, we replaced 14 solvent-exposed hydrophobic residues of acetylcholinesterase by arginine. The stabilities of the resulting proteins were tested using denaturation by high temperature, organic solvents, urea and by proteolytic digestion.ConclusionAltough the mutational effects were rather small, this strategy proved to be successful since half of the mutants showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(51 citation statements)
references
References 38 publications
6
44
0
Order By: Relevance
“…All of the mutants exhibited a similar broad negative band with similar intensity in the mean residue ellipticity. The results reveal that the aromatic side chains of Tyr 32 , Trp 39 , and Trp 83 experience the same steady and compact tertiary environment as seen in the native apoNCS.…”
Section: Cloning and Characterization Of Recombinant Aponcs Proteins-af-supporting
confidence: 49%
See 1 more Smart Citation
“…All of the mutants exhibited a similar broad negative band with similar intensity in the mean residue ellipticity. The results reveal that the aromatic side chains of Tyr 32 , Trp 39 , and Trp 83 experience the same steady and compact tertiary environment as seen in the native apoNCS.…”
Section: Cloning and Characterization Of Recombinant Aponcs Proteins-af-supporting
confidence: 49%
“…The denaturation curves ( The observed T m values for L77A and D79A are slightly smaller (6 and 4°C) than that of WT apoNCS. This is not surprising, considering the well known fact that charged residues at surface can stabilize proteins (39). Likewise, replacing the large hydrophobic residues with small ones can also reduce stability (39,40).…”
Section: Cloning and Characterization Of Recombinant Aponcs Proteins-af-mentioning
confidence: 96%
“…5d) can change electrostatic interactions because of the additional arginine residues. Previous studies have demonstrated that enhanced surface charge-charge interactions due to arginine substitutions are crucial to the improved thermal stability of modified enzymes [29,30]. The modeled structure of CESH shares significant resemblance to haloacid and haloacetate dehalogenases whose structures contain two domains that are referred to as the core and cap domains.…”
Section: Saturated Mutagenesismentioning
confidence: 96%
“…MSAs is an effective tool in predicting potential hot-spots for substitution to improve enzyme properties [13,29]. Within the same superfamily, amino acid residues that are shared by thermally stable proteins but not by thermally vulnerable proteins may be crucial to the thermostability.…”
Section: Multiple Sequence Alignmentsmentioning
confidence: 99%
“…It is known that polar and charged amino acids primarily cover the surface of proteins and usually associate with each other. Positively charged amino acids form salt bridges with charged residues, and this noncovalent interaction is crucial because it provides stability to the folded protein conformation (42,43). Thus, it is likely that the arginine residue is responsible for maintaining a stable conformation of the modulatory region of Mid1.…”
Section: Discussionmentioning
confidence: 99%